2022
DOI: 10.1155/2022/3238613
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Analgesia for Pain Management in Acute Pancreatitis during Pregnancy and Its Effect on Maternal and Fetal Outcome

Abstract: Background. Acute pancreatitis (AP) during pregnancy is a rare presentation with an estimated incidence of 1 case per 1000 to 10,000 pregnancies. Severe epigastric and abdominal pain is the earliest and the most common symptom of AP, and adequate pain relief is an integral part of patient management. The aim of our study was to investigate the different pain relief modalities that are used in pregnant women with AP and the efficacy of each method used, in terms of better pain relief and maternal-fetal outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several studies have supported the use of epidural anesthesia in pregnant patients undergoing C-section, as it provides excellent analgesia, minimizes the need for opioids, and allows for early mobilization [ 26 ]. Dogra et al [ 27 ] investigated the efficacy of epidural anesthesia compared to general anesthesia on maternal-fetal outcomes and pain relief. Their findings showed that epidural anesthesia was better compared to intravenous anesthesia in terms of pain management and recovery of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have supported the use of epidural anesthesia in pregnant patients undergoing C-section, as it provides excellent analgesia, minimizes the need for opioids, and allows for early mobilization [ 26 ]. Dogra et al [ 27 ] investigated the efficacy of epidural anesthesia compared to general anesthesia on maternal-fetal outcomes and pain relief. Their findings showed that epidural anesthesia was better compared to intravenous anesthesia in terms of pain management and recovery of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is expected to occur in 1–10 births per every one thousand 1 , 2 . It is a potentially catastrophic obstetric complication for mom and baby alike.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn decreases the risk of pancreatic necrosis. Reduced morbidity from AP is attributable to epidural analgesia since it prevents pancreatic necrosis and its other negative consequences 10 . Although preliminary research on its effectiveness in AP is encouraging, further information is needed.…”
Section: Introductionmentioning
confidence: 99%